Development of Character-Based E-Module Design to Improve Elementary School Students' Experiences - Wijayanti, Ervina; Qomariah, Nurul; Felisima Tae, Lidwina (IJCAR: Indonesian Journal of Classroom Action Research, 2024)
Increasing the development of students' character values in schools is a potential strategy to address the moral crisis that the education sector is currently going through, which is causing negative behavioral changes in students. Not only could attitudes be utilized to instill character qualities, but educational media can also be utilized to facilitate learning. To enhance the caliber of instructional resources and refine the pedagogical abilities of teachers, learning media could be adapted by several resources in changing times. Therefore, one of the methods is to use character-value-laden electronic modules as instructional materials. This study aims to determine whether using this e-module could help students learn more effectively in the classroom and develop their character. The character-based E-Module is suitable for use as a learning tool and has the potential to help students develop their character in the classroom, according to findings from several sources gathered through the literature study technique. However, we recommend that future studies elaborate on the character impact of the students learning in classroom activities by using other learning media.